SHRAMAHARA MAHAKASHAYA OF CHARAKA SAMHITA – A PROMISING SUPPLEMENT FOR IMMUNOMODULATION – A SYSTEMATIC REVIEW - Dharmasena, K N A; Ramamurthy, A; Krutika, Joshi; Sahrma, Gaurav (International Research Journal of Ayurveda & Yoga, 2019)
Immuno-modulation or modification of the immune responses towards wellbeing is incorporated as vyadhik shamatva, swasthya (wellbeing), bala(strength) and ojas in Ayurveda. Shrama (fatigue) is the main feature of balakshaya (Strength depletion), ojahkshaya (condition of depleting immunity) as well as rasa, asthi and shukradhatu kshaya (tissue depletions). Thereby, shrama and vyadhik shamatva have a coexisting relation. Acharya Charaka has collectively mentioned 10 drugs as shramahara mahakashaya which works effectively in shrama. Ingredients of shramahara mahakashaya are rich in nutrients, antioxidants and also have proven effects on anxiety, and in immuno-modulation. Hence, this systematic review has been carried out to find the efficacy of shramahara mahakashaya in immuno-modulation. The study was carried out using thorough analysis of various Ayurveda classical texts as well as available modern literature and collected data & observations were presented in a scientific manner. The review will be beneficial to understand and to modify the host immunity according to Ayurveda concepts.